Turbine Efficiency Measurement System for the QinetiQ Turbine Test Facility - Beard, P; Povey, T; Chana, K (2010)
A turbine efficiency measurement system has been developed and installed on the turbine test facility (TTF) at QinetiQ Farnborough. The TTF is an engine-scale short-duration (0.5 s run time) rotating transonic facility, which can operate as either single stage (HP vane and rotor) or 11/2 stage (HP stage with IP or LP vane). The current MT1 HP stage is highly loaded and unshrouded and is therefore relevant to current design trends. Implementation of the efficiency measurement system forms part of the EU Turbine Aero-Thermal External Flows (TATEF II) program. The following aspects of the efficiency measurement system are discussed in this paper: mass-flow rate measurement, power measurement by direct torque measurement, turbine inlet and exit area traverse measurement systems, computation of efficiency by mass weighting, and uncertainty analysis of the experimentally determined turbine efficiency. The calibration of the mass-flow rate and torque measurement systems are also discussed. Emphasis was placed on the need for a low efficiency precision uncertainty, so that changes in efficiency associated with turbine inlet temperature distortion and swirl can be resolved with good accuracy. Measurements with inlet flow distortion form part of the TATEF II program and will be the subject of forthcoming publications. © 2010 by ASME.